Online Assessment Literacy of In-Service EFL Teachers: A Cross-Sectional Study of Competency Levels and Demographic Factors - Ziddan Marsa Utama; A. A. Gede Yudha Paramartha; Luh Gede Eka Wahyuni (English Education Department STKIP Agama Hindu Singaraja, 2026)
Online assessment literacy (OAL) has become increasingly important as teachers are expected to design, implement, and evaluate assessments in technology-enhanced learning environments. However, limited evidence is available regarding teachers’ OAL levels and the influence of demographic characteristics on these competencies, particularly in the Indonesian context. This study aimed to investigate the online assessment literacy of in-service English as a Foreign Language (EFL) teachers in junior high schools and examine whether demographic factors influence their OAL scores. A quantitative cross-sectional survey design was employed. Data were collected from 48 in-service EFL teachers in Jembrana Regency, Bali, Indonesia, using an adapted version of the Assessment Literacy Inventory. The instrument consisted of 28 objective items covering seven assessment competency domains. Descriptive statistics were used to determine teachers’ OAL levels, while independent-samples t-tests were conducted to examine differences across demographic variables, including gender, educational background, teaching experience, school type, and certification status. The findings revealed that the overall level of OAL was categorized as fair (M = 15.42, SD = 2.89), with 56.25% of participants classified in the fair category and 35.42% in the good category. Among the assessed dimensions, teachers demonstrated stronger competencies in using assessment results for instructional decision-making and administering online assessments, while lower performance was observed in developing assessment instruments and recognizing ethical issues in online assessment. Furthermore, no statistically significant differences were found across any demographic variables (p > .05), indicating that gender, educational background, teaching experience, school type, and certification status did not significantly influence OAL scores. The study concludes that although teachers possess a basic understanding of online assessment practices, further professional development is needed to strengthen competencies related to assessment design and ethical assessment practices. The findings highlight the importance of continuous training and institutional support in enhancing teachers’ online assessment literacy in technology-enhanced learning environments.